Association Between Body Mass Index and Infertility Among Women: An Age-Matched Case-Control Study - K, Myl Kumaran; D, Raja; A.Y, Nirupama (Asian Journal of Interdisciplinary Research, 2024)
Ample literature exists which time and over has established the association between overweight/ underweight and fertility problems. Further in this context, it should be noted that there are very few studies in the Indian context regarding the effect of body mass index (BMI) on infertility in women. To evaluate the association of BMI with infertility among women in Tamil Nadu, India. An age-matched hospital-based case-control study was conducted including 204 women attending a tertiary care hospital in the Chengalpattu district of Tamil Nadu. Of these, 102 women who had a clinical diagnosis of infertility were selected as cases. Hospital controls were defined as women who did not have a clinical diagnosis of infertility and were selected after matching for age and years of marriage (± 2 years). BMI was calculated from the height and weight measurements taken during the time of recruitment to the study. Basic socio-demographic data were also collected from all the study participants. Among cases, 17.6% were underweight, 25.5% were overweight and 5.9% were obese. Whereas, among controls, 7.8% were underweight, 47.1% were overweight and 11.8% were obese. Among the cases, 68% had primary infertility and 32% had secondary infertility. Overweight and obese women had 2.82 odds (95% CI, 1.48 – 5.38) and 3.06 odds (95% CI, 1.05 – 8.93) respectively of having infertility when compared to women who fell within the normal BMI range. Both overweight and obesity were observed to be significantly associated with infertility. The focus should be given to the prevention and control of both as an effective means of reducing the risk of infertility and other associated disorders.